Study on stage division and evaluation index of microwave deicing technology for pavement concrete - Tao Chen; Ying Zhang; Biao Ren; Yan Lv; Tao Ge; Erlei Bai; Li Wang (Scientific Reports)
Abstract Microwave deicing technology has received growing attention as one of the deicing solutions for road surface icing in cold climates due to its benefits, such as energy savings, environmental protection, high efficiency, pavement protection, and others. In this study, practical and theoretical research was conducted on the stage division of the physical process of microwave deicing of road surface concrete and the deicing technology assessment index. Based on the experimental results and the characteristics of ice melting, the microwave deicing process can be divided into four stages, respectively: Heat from Concrete Stage (HCS), Heat from Water Stage (HWS), Ice Thinning Stage (ITS), and Ice Breaking and Melting Stage (IBMS). Five indicators may be used to evaluate the deicing efficiency of road surface deicing technology: the time when the temperature of the concrete surface reaches 0 ℃, the time when the water layer is fully formed, the time spent from the complete formation of the water layer to ice breaking, the deicing area and the ice breaking area. The microwave deicing efficiency of road surface concrete can be improved by combining carbon fibers in the concrete, and the enhancing impact varies with carbon fiber length. When the length of the carbon fiber is 0.6 cm, the deicing speed of the concrete specimen is 2.0 times faster than that of the concrete specimen without the carbon fiber, and the deicing area is 1.2 times larger.